To find 2 times the sum of y and 5, you first need to calculate the sum of y and 5 by adding y and 5 together. Once you have the sum, you then multiply it by 2 to find the final result. The expression for this calculation would be 2(y + 5).
That verbal expression would read: 3(x+y)^2 + 5(2x -y) ^2 means 'squared' in the above example.
To find 4 times the sum of y and 7, you first calculate the sum of y and 7, which is y + 7. Then, you multiply this sum by 4 to get the final result. Therefore, the expression for 4 times the sum of y and 7 is 4(y + 7), which simplifies to 4y + 28.
Let x = one number = 2 or 2.5 Let y = the other number = 2.5 or 2 (x)(y)=5 x+y=4.5 y=4.5-x (x)(y)=5 (x)(4.5-x)=5 4.5x-x^2-5=0 I used the quadratic formula to get x. x=2 or x=2.5 (x)(y)=5 (2)(y)=5 y=5/2 y=2.5 (x)(y)=5 (2.5)(y)=5 y=5/2.5 y=2
x^(4)*y*x^(5)*yMultiply x^(4) by y to get x^(4)y.(d)/(dx) x^(4)*y*x^(5)*y=x^(4)y*x^(5)*yMultiply x^(4)y by x^(5) to get x^(9)y.(d)/(dx) x^(4)*y*x^(5)*y=x^(9)y*yMultiply x^(9)y by y to get x^(9)y^(2).(d)/(dx) x^(4)*y*x^(5)*y=x^(9)y^(2)To find the derivative of x^(9)y^(2), multiply the base (x) by the exponent (9), then subtract 1 from the exponent.(d)/(dx) x^(4)*y*x^(5)*y=9x^(8)y^(2)The derivative of x^(4)*y*x^(5)*y is 9x^(8)y^(2).9x^(8)y^(2)
2(y + 5)
To find 2 times the sum of y and 5, you first need to calculate the sum of y and 5 by adding y and 5 together. Once you have the sum, you then multiply it by 2 to find the final result. The expression for this calculation would be 2(y + 5).
5(x^2 + y)
To find 2 times the sum of x and y, you first need to calculate the sum of x and y by adding the two variables together. Once you have the sum, you multiply it by 2 to get the final result. In mathematical terms, the expression for 2 times the sum of x and y can be written as 2(x + y).
That verbal expression would read: 3(x+y)^2 + 5(2x -y) ^2 means 'squared' in the above example.
5
3[(x^2) + 5] x (2x-y) Do the parentheses first, then brackets next. P.e.m.d.a.s.
To find 4 times the sum of y and 7, you first calculate the sum of y and 7, which is y + 7. Then, you multiply this sum by 4 to get the final result. Therefore, the expression for 4 times the sum of y and 7 is 4(y + 7), which simplifies to 4y + 28.
Let x = one number = 2 or 2.5 Let y = the other number = 2.5 or 2 (x)(y)=5 x+y=4.5 y=4.5-x (x)(y)=5 (x)(4.5-x)=5 4.5x-x^2-5=0 I used the quadratic formula to get x. x=2 or x=2.5 (x)(y)=5 (2)(y)=5 y=5/2 y=2.5 (x)(y)=5 (2.5)(y)=5 y=5/2.5 y=2
5 x 17 = 85 85 + Y so therefore it equals 100 + 10 = 110
Twice the sum of 'x' and 'y' . . . 2(x+y) The sum of twice 'x' and 'y' . . . (2x+y)
2(2+Y)